Two new species of Rhodiola (Crassulaceae) from the Qinghai-Tibetan Plateau - Zhang, Jianqiang; Meng, Shi-Yong; Rao, Guang-Yuan (Phytotaxa, 2015)
Two new species, Rhodiola daochengensis, and Rhodiola tricarpa (Crassulaceae) were described from the Qinghai-Tibetan Plateau, China. Rhodiola daochengensis was placed in sect. Rhodiola due to its dioecy, cymose inflorescences, and sessile, serrate stem leaves. It shares close morphological affinity with R. kirilowii which is supported by the ITS data but differed from the latter in the morphology of leaves (amplexicaul, cordate at base of leaves), flower stems, and pedicel (with densely glandular-pubescent) and fruits (apical beak recurved strongly). Rhodiola tricarpa is unique for its tricarpellary pistil and belongs to sect. Chamaerhodiola due to its dioecy and elongate flowering stems. It shares morphological affinity with R. coccinea, R. fastigiata and R. tangutica but differs in caudex leaves (dimorphic), and flowers (3-merous).